Robust nonlinear control for hypersonic vehicles subject to parameter uncertainties and external disturbances - Kuo, Li; Weijia, Duan; Hao, Liu; Lingyi, Yu (2015 34th Chinese Control Conference (CCC), 2015)
The dynamical characteristics of hypersonic vehicles make them challenging to achieve the robust flight. The vehicle dynamics involve parametric uncertainties, serious coupling, nonlinearity, unmodeled uncertainties and external disturbances. A robust nonlinear controller is proposed consisting of a feedback linearization controller and a linear robust controller to restrain the effect of the multiple uncertainties. The feedback linearization method is firstly applied to achieve the output/input exact linearization for the longitudinal model, which results in a linear model. Then, a linear robust controller including a nominal controller and a robust compensator is designed based on the obtained linear model. The nominal controller is designed based on the pole assignment algorithm to guarantee that the outputs of the nominal linear closed-loop system can track the desired references for the velocity and height channels, whereas the robust compensator is introduced to restrain the effects of parametric uncertainties and external disturbances on the closed-loop control system. Numerical simulation results are given to verify the robustness and the effectiveness of the proposed robust nonlinear control method.